(untitled) (Research, Society and Development, 2022)
Before the arrival of the Portuguese Royal Family in 1808, there was no science in Brazil, only chronicles and reports from travelers and missionaries, so it was up to the French priest Ivo D’Evreux to make ethnographic records about the way of life and customs of the Tupinambás people, as well as descriptions of flora and fauna in Maranhão. The general objective of this study was to rescue the natural history of Maranhão’s past flora in the XVII century, referring to utilitarian plants, through documental research of the work A Viagem ao Norte do Brasil written by Father Ivo D’Evreux, seeking, more specifically, to know the species, their origins and their uses. Seventeen ethnomonads were extracted, of which 88.2% (n=15) were identified at the level of family, genus and species, and 11.8% (n=2) did not have their botanical identities identified. Of the total, 83.3% (n=14) are composed of native species and 17.6% (n=3) of exotic species. Regarding uses, human food had the highest rate of citations 35.3% (n=6). The uses were utensils and oils/oils/oils with 22.2% (n=4) and construction with 17.6% (n=3). These results show the use of the floristic biodiversity found at that time. Studies of this nature contribute to greater knowledge and research regarding centers of origin and dispersal of species, domestication, human displacement, extinction of local species and development of new products, among other possibilities.